مضاربہ: اسلامی مالیات کے تناظر میں ایک جامع تجزیاتی مطالعہ: Mudarabah in Islamic Finance: A Comprehensive Analytical Study - Dr. Abdul Rauf,; Maryam Mumtaz, (Al-Amīr Research Journal for Islamic Studies, 2025)
Mudarabah is a key contractual arrangement in Islamic finance that embodies the principles of partnership, risk-sharing, and Shariah compliance. It is based on cooperation between two parties: the Rab al-Māl, who supplies the financial capital, and the Mudarib, who manages the business venture by contributing expertise, effort, and managerial skills. Under this arrangement, capital and labor are treated as complementary and equally valued inputs in the production process. A defining feature of Mudarabah is the complete prohibition of interest (riba), as returns to the investor are neither fixed nor guaranteed. Instead, profits are shared between the parties according to a pre-agreed ratio determined at the inception of the contract. In the event of a business loss, the Rab al-Māl bears the financial loss, while the Mudarib incurs the loss of time, effort, and labor, receiving no monetary compensation, provided no negligence or misconduct has occurred. This risk allocation reflects the underlying principles of justice and balance inherent in Islamic economic thought. Mudarabah holds a distinctive position within Islamic banking and finance due to its contribution to wealth circulation, entrepreneurship development, and employment generation. By linking financial returns to real economic activities and lawful trade, it promotes transparency, fairness, and ethical conduct. Consequently, Mudarabah extends beyond a profit-oriented mechanism to function as a socially responsible financial model that supports equitable wealth distribution and the broader objectives of Islamic social and economic justice. Keywords: Mudarabah, Rab al-Māl, Mudarib, Islamic Finance, Profit-and-Loss Sharing, Islamic Banking